New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East - Samartsev, Konstantin G. (Zootaxa, 2018)
Four new species from the Russian Far East, Bracon kasparyani sp. nov., B. kotenkoi sp. nov., B. santachezae sp. nov. and Uncobracon belokobylskii sp. nov., are described and short keys for their identification are presented.